2013
DOI: 10.1007/s12639-013-0354-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ixodid ticks in dairy animals of Jammu region

Abstract: To determine the prevalence of ticks, 960 bovines (cattle 480, buffaloes 480) were examined from organised and unorganised dairy units of Jammu district during March 2012 to February 2013. The overall infestation rate was found to be 42.18 %. The infestation rate in cattle was found to be 47.08 % while 37.29 % of examined buffaloes were infested with ixodid ticks. Among the ixodid ticks, only one species i.e. Rhipicephalus (Boophilus) microplus was recorded. A significantly (p < 0.05) higher prevalence was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…Highest prevalence of mixed infections in donkeys was observed in monsoon (32 %) followed by winter (27.59 %) and summer (24 %). Pramod (2010) reported much lower prevalence rates from Nagpur, Maharashtra while Mahfooz et al (2008) and Khajuria et al (2004) support the present study.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Highest prevalence of mixed infections in donkeys was observed in monsoon (32 %) followed by winter (27.59 %) and summer (24 %). Pramod (2010) reported much lower prevalence rates from Nagpur, Maharashtra while Mahfooz et al (2008) and Khajuria et al (2004) support the present study.…”
Section: Resultssupporting
confidence: 84%
“…In contrast, distinctly higher prevalence was reported by many workers viz. Khajuria et al (2004), Pandit et al (2008) and Maria et al (2011) from Jammu and Kashmir; Kaur and Kaur (2008) from Punjab, Katoch et al (2006) from Haryana, Sengupta and Yadav (1998) from Himachal Pradesh, Fig. 1 Intensity of gastrointestinal helminth infection in equids Sengupta and Yadav (2001b), Banerjee et al (2002) and Pal (2002) from UP and Uttrakhand.…”
Section: Resultsmentioning
confidence: 99%
“…The overall prevalence of gastrointestinal nematodes observed in the present study have also been reported by Khajuria et al, (2004) and Pandit et al, (2008) in Jammu and Kashmir, Katoch et al, (2006) in Haryana and (Sengupta and Yadav, 1998) in Himachal Pradesh in their studies. Further, Singh et al (2012) found 75.73% which is higher than the results of the present study.…”
Section: Prevalence Of Gastrointestinal Nematodesupporting
confidence: 90%
“…The agro-climatic conditions of the Jammu region are highly favourable for growth and multiplication of ticks which act as natural vectors of theileriosis, babesiosis and anaplasmosis. In the present study, high prevalence of Babesia bigemina (14.02%, 39/278), A. marginale (23.74%, 66/278) and low prevalence of Theileria annulata (1.079%, 3/278) can be attributed to Rhipicephalus (Boophilus) microplus being the only tick which infests the bovines of Jammu region [12]. A thorough review of literature reveals varying incidence of babesiosis ranging from 0.76 to 18.50% in India [13,14,15].…”
Section: Discussionsupporting
confidence: 45%